2015
DOI: 10.1007/s11121-015-0544-0
|View full text |Cite
|
Sign up to set email alerts
|

Program and Teacher Characteristics Predicting the Implementation of Banking Time with Preschoolers Who Display Disruptive Behaviors

Abstract: This study examined the relationship among baseline program and teacher characteristics and subsequent implementation of Banking Time. Banking Time is a dyadic intervention intended to improve a teacher's interaction quality with a specific child. Banking Time implementation was examined in the current study using a sample of 59 teachers and preschool children displaying disruptive behaviors in the classroom (~three children per classroom). Predictors included preschool program type, teacher demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…With respect to practice and policy, school leaders should consider additional training and supports for teachers to form and maintain positive relationships with all of their students, perhaps even coaching teachers to build and manage effective relationships with children with whom they have more conflictual relationships or who are at higher risk for negative outcomes (e.g., Williford, Wolcott, Whittaker, & LoCasale‐Crouch, 2015). The implications for policy of this study, if replicated, could affect decisions to place children with certain teachers, in addition to in‐service training for teachers of young children.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to practice and policy, school leaders should consider additional training and supports for teachers to form and maintain positive relationships with all of their students, perhaps even coaching teachers to build and manage effective relationships with children with whom they have more conflictual relationships or who are at higher risk for negative outcomes (e.g., Williford, Wolcott, Whittaker, & LoCasale‐Crouch, 2015). The implications for policy of this study, if replicated, could affect decisions to place children with certain teachers, in addition to in‐service training for teachers of young children.…”
Section: Discussionmentioning
confidence: 99%
“…The perspective that student–teacher relationships are important for teachers as well as for students might also motivate practitioners to enhance relationship quality and to detect possible sources of meaningful change. For example, the intervention program Banking Time, designed to enhance relational quality between a teacher and a preschooler might provide evidence-based practical suggestions as to how congruent close relationships in the classroom can be fostered ( Williford et al, 2015 ). This intervention program focuses on secluded teacher–child interaction time in which the teacher is asked (1) to observe the child’s behavior and emotions, (2) to narrate the child’s actions and to follow their intentions, (3) to label the child’s emotions in order to understand the child’s perspective and (4) to incorporate relevant relational themes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Little et al (2013) found that teacher self-efficacy partially mediated the effect of training on treatment integrity in a dissemination trial of a school-based prevention program. However, recently Williford, Wolcott, Whittaker, and Locasale-Crouch (2015) did not find an association between teacher self-efficacy and teacher integrity of Banking Time, a tier-2 early childhood intervention. In the current study, we hypothesized that teachers who had higher levels of self-efficacy at the outset of the study would be more likely to implement BEST in CLASS extensively and with competence than would teachers who had lower levels of self-efficacy.…”
Section: Rationale For the Current Studymentioning
confidence: 91%
“…Teachers' education background has also been hypothesized to be associated with program delivery (Domitrovich et al, 2008;Durlak, 2010) and research suggests that teachers' education is related to program quality (Pianta et al, 2005). Williford et al (2015) found that teachers with an early childhood education major provided greater dosage of Banking Time than teachers without an early childhood degree. Therefore, in the current study we hypothesized that teachers with more education would implement BEST in CLASS more extensively and with greater competence than would teachers with less training.…”
Section: Rationale For the Current Studymentioning
confidence: 99%